Structural investigation of low energy ion irradiated Al2O3. Issue 16 (November 2019) - Kumar, Sunil; Shah, Sejal; Sulania, Indra; Singh, Fouran; Chakraborty, Arun
Abstract: The present study is undertaken to investigate the ion irradiation impact on the structural properties of α-Al2 O3 which is one of the potential insulator used for ITER-like reactors. 300 keV Ar 6+ ion beam with varying fluence is used to irradiate Al2 O3 polycrystalline material in bulk form. Structural damage to α-Al2 O3 due to ion irradiation is investigated by grazing incidence XRD (GIXRD), micro-RAMAN and photoluminescence spectroscopy. Further, the surface morphology of irradiated and pristine samples is studied using atomic force microscopy. GIXRD data reveal the radiation induced damage at low fluence and structural improvement at higher fluence up to 1 × 10 16 ions/cm 2 . Annealing effect is explained by temperature rise during irradiation and due to partial grain growth of Al2 O3 at 1 × 10 16 ions/cm 2 . It is important to note that there is no sign of amorphization even at the highest fluence 1 × 10 16 ions/cm 2 used in this study. The explanation is supported by the Raman characterization results. Detailed peak assessment of photoluminescence spectra is presented. Photoluminescence characterization results are corroborated with XRD results. The present study reveals the radiation hardness of polycrystalline Al2 O3 material in the low energy ion regime.